2015
DOI: 10.1161/hypertensionaha.114.04435
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dietary Intake of Polychlorinated Biphenyls and the Incidence of Hypertension in a Spanish Cohort

Abstract: Polychlorinated biphenyls are persistent organic pollutants that are consumed because of their bioaccumulation through the food chain. Evidence from different sources suggests a positive association between polychlorinated biphenyls exposure and the incidence of hypertension. However, no previous prospective study has investigated this potential relationship in adults. We prospectively assessed the association between dietary intake of polychlorinated biphenyls and the incidence of hypertension in a large coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Interestingly, mice with a compromised liver and exposed to Aroclor1260 displayed signs of endothelial cell dysfunction (increased plasma ICAM-1, P-Selectin and thrombomodulin). Furthermore, studies on PCB exposure and hypertension are scarce, with only a few epidemiologic studies showing associations between plasma PCBs and increased risk for hypertension (Donat-Vargas et al 2015; Park et al 2016). Recently, a study by our group has reported an increase in hepatic Fmo3 expression with “dioxin-like” PCBs, thereby implicating these pollutants as risk factors for CVD (Petriello et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mice with a compromised liver and exposed to Aroclor1260 displayed signs of endothelial cell dysfunction (increased plasma ICAM-1, P-Selectin and thrombomodulin). Furthermore, studies on PCB exposure and hypertension are scarce, with only a few epidemiologic studies showing associations between plasma PCBs and increased risk for hypertension (Donat-Vargas et al 2015; Park et al 2016). Recently, a study by our group has reported an increase in hepatic Fmo3 expression with “dioxin-like” PCBs, thereby implicating these pollutants as risk factors for CVD (Petriello et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Because miRNAs have been proposed as biomarkers for diseased states (Wang et al, 2016), they can also potentially be used as biomarkers for PCB exposure and PCB-induced diseases. Environmental exposure to PCBs have been positively correlated to various diseases directed to either a particular or multiple organ systems such as non-alcoholic fatty liver disease, non-alcoholic steatosis, diabetes and insulin resistance, obesity, and hypertension, myocardial infarction and stroke (Bergkvist et al, 2015; Bergkvist et al, 2014; Cave et al, 2010; Donat-Vargas et al, 2015). Furthermore, a number of diagnostic markers have been proposed for PCB exposure such as elevated serum liver enzymes and elevated cholesterol and triglycerides which are risk factors for either liver diseases or cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A fourth large follow-up study also was conducted in Spain with 1,497 cases of hypertension among 14,521 participants; the median follow-up was 8.3 y (Donat-Vargas et al 2015). PCB concentrations were not measured.…”
Section: Evidence From Longitudinal Studiesmentioning
confidence: 99%
“…Most studies analyzing the connection between PCBs and hypertension are cross-sectional (Everett et al 2008;Goncharov et al 2011;Henríquez-Hernández et al 2014;Yorita Christensen and White 2011;Peters et al 2014) as are those linking dioxin-like compounds and hypertension (Chang et al 2010;Ha et al 2009;Ilhan et al 2015;Lee et al 2007;Uemura et al 2009;Nakamoto et al 2013). Cohort studies have been used infrequently, with only a few conducted to assess POPs and hypertension incidence (Arrebola et al 2015;Donat-Vargas et al 2015Raffetti et al 2018).…”
Section: Introductionmentioning
confidence: 99%